Gaya Komunikasi Dalam Organisasi Mapala Stacia Universitas Muhammadiyah Jakarta - Fina Abiyya Agustin Mubarokah; Rima Damayanti; Hawa Arofah Qudsy; Sabrina Humaira Darmawy; Jamiati KN (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research aims to find out what communication styles are used in the Mapala Stacia Umj UKM organization. The communication styles used definitely vary, because it can be seen from members who come from various faculties, of course everyone has a communication style that they use. The purpose of this research is to examine the influence of the communication style used in the Mapala Stacia UKM organization. The Mapala Stacia organization is a group of nature lovers dedicated to promoting environmental awareness and natural activities. With a focus on climbing, nature research and environmental conservation, Mapala Stacia is committed to forming a generation that is aware of the importance of conserving biodiversity. This research is qualitative research using interview techniques with one of the members of Mapala Stacia, Muhammadiyah University, Jakarta. Researchers want to know more specifically the communication style used in the Mapala Stacia UKM organization. The results of research conducted by researchers are that the communication style used is a non-formal communication style but remains polite in communicating between leaders and members, or members and members, cultural background does not hinder the communication process within the Mapala Stacia Umj organization in discussing a matter.